Wastewater reuse for irrigation and seawater intrusion: Evaluation of salinity effects on soils in Cyprus - Kathijotes, Nicholas; Panayiotou, Charalambos (My University, 2014)
Climate change and the continuous population growth increase the demand for water, which in arid and semiarid regions, like the Mediterranean, is considered a limited resource. Future demands will not be met by traditional water resources like surface and groundwater. In order to handle increased water demand, the treated wastewater originating from municipal wastewater treatment plants is offered to farmers for agricultural irrigation. Over pumping of fresh groundwater creates seawater intrusion that causes various problems, besides others, to the quality of recycled water used for agricultural purposes. The effects on soils irrigated with saline water are investigated. Actual investigations were carried out in land irrigated with salinity-affected wastewater and non-irrigated land nearby. Soil profile analyses are demonstrated and compared, showing very interesting results and adverse effects on soil resources. Irrigation with saline waters even at slightly above recommended values can have severe effects on soil resources. Various remediation scenarios for preventing seawater intrusion, as well for mitigation or control of soil salinity problems, are also suggested in this study. This case study was carried in the Larnaca district in Cyprus.
Keywords: Agricultural irrigation; Electric conductivity; Salinity; Sodium absorption ratio; Wastewater reuse